Clinical significance of preoperative Glasgow prognostic score in patients with colorectal cancer and synchronous peritoneal metastases - Kosuke Fujimoto; Fumikazu Koyama; Hirotoshi Kobayashi; Kenjiro Kotake; Masayasu Kawasaki; Yukihide Kanemitsu; Yusuke Kinugasa; Hideki Ueno; Kotaro Maeda; Takeshi Suto; Michio Itabashi; Kimihiko Funahashi; et al. (Annals of Gastroenterological Surgery)
Abstract Background Chemotherapy is the typical choice for treating colorectal cancer with synchronous peritoneal metastases. Nonetheless, surgical resection may be chosen if the metastases are resectable. Unfortunately, there is no reliable preoperative or intraoperative prognostic indicator. This study aimed to determine the prognostic significance of the preoperative Glasgow prognostic score (GPS) in colorectal cancer patients with synchronous peritoneal metastases. Methods We conducted a prospective study on 143 patients with colorectal cancer and concurrent peritoneal metastases. Our analysis included prognostic factors, such as the GPS, using data from the institutional observational study by the Japanese Society for Cancer of the Colon and Rectum. Results The 3‐year survival rates for the GPS0 or 1 and GPS2 groups were 32.7% and 14.3%, respectively, with a significantly worse prognosis in the GPS2 group (p = 0.003). Multivariate analysis identified GPS2 (p = 0.006) and the peritoneal cancer index (PCI) (p = 0.029) or the Japanese surgical peritoneal metastasis grade (p = 0.009) as independent poor prognostic factors. Additionally, the GPS0 or 1 group with total resection of peritoneal metastases had a significantly better prognosis than the non‐resection group (p < 0.001); however, there was no difference between the GPS2 group with total peritoneal resection and the non‐resection group (p = 0.713). Conclusions Preoperative GPS2 is an independent poor prognostic factor in patients with colorectal cancer and synchronous peritoneal metastases, and surgical resection does not improve prognosis in patients with GPS2. Preoperative GPSs may be used as indicators for surgical resection of synchronous peritoneal metastases.